2014
DOI: 10.1007/s40596-014-0215-7
|View full text |Cite
|
Sign up to set email alerts
|

Women for a Change: Closing the Leadership Gap

Abstract: In the fall of 2013, the first author (SS) attended the Association for Academic Psychiatry's annual meeting in Charleston, South Carolina. During a panel discussion on the second day, the issue of why there are so few women leaders in psychiatry did not simply emerge-it exploded, so much so that it was a challenge for the highly skilled facilitator of the discussion to move the conversation away from gender and into other areas of navigating a career as a psychiatric educator. At the workshops, conversations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…These characteristics are known as feminine attributes, such as strong communication skills, advanced intermediary skills and empathy towards others (Stanford et al, 1995). Still, we found that no country has yet closed the gender gap at the organisational level (Soklaridis & López, 2014). The continuous underrepresentation of females in high positions in many countries shows a significant gender bias in hiring and promoting leaders (Eagly & Karau, 1991, 2002; Hoobler et al, 2014; Player et al, 2019).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…These characteristics are known as feminine attributes, such as strong communication skills, advanced intermediary skills and empathy towards others (Stanford et al, 1995). Still, we found that no country has yet closed the gender gap at the organisational level (Soklaridis & López, 2014). The continuous underrepresentation of females in high positions in many countries shows a significant gender bias in hiring and promoting leaders (Eagly & Karau, 1991, 2002; Hoobler et al, 2014; Player et al, 2019).…”
Section: Introductionmentioning
confidence: 78%
“…Various social and cultural barriers are found in most of the South Asian countries (Sabharwal, 2013). However, if organisations are also supportive to consider policy changes, quotas and formal mentoring programmes, women leaders will certainly achieve their expected position in the organisation (Bhatnagar, 2008; Sabharwal, 2013; Soklaridis & López, 2014). The study also revealed the fact that women leaders need to be self-motivated, even if they are getting support in their career development process (Bhatnagar, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One key organizational obstacle to recruiting, hiring, and promoting women leaders is homophily (Soklaridis & Lopez, 2014). An attraction paradigm is whereby individuals possess more positive attitudes and evaluations about people whom they see as similar to themselves.…”
Section: Praxismentioning
confidence: 99%
“…Soklaridis (12) described the importance of mentors in academic life and the notion of homophily people's preference for associating with similar others. Mentorship is not practiced formally in Iranian medical universities.…”
Section: Mentorship Programsmentioning
confidence: 99%